Antena Mikrostrip Circular Patch untuk Aplikasi Radar Altimeter pada Frekuensi C-Band Menggunakan Metode Parasitik - Siti Latifah; Hanny Madiawati (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
Currently, human mobility and traffic between regions and between countries are increasing, this requires the world of aviation to grow as well. One of the developments in the world of aviation is radar altimeter technology as an aircraft navigation system that works in the frequency range of 4.2 - 4.4 GHz. In this research, the realization of a microstrip antenna with a circular patch on the C-band frequency has been carried out with the addition of parasitic elements and proximity coupled feeding to strengthen the gain and widen the bandwidth. The antenna is made using Rogers RT5870 material which has a relative permittivity of 2.33, a material thickness of 1.575 mm and a loss tangent of 0.0012. The measurement results show that the bandwidth of 300 MHz is 3.54% narrower than the simulation results, while the gain is 4.79% to 8.13 dBi and the radiation pattern is unidirectional.